Promoting Green Campus Awareness through BIOMAGIC: User Evaluation of a Black Soldier Fly Educational Flipbook among Biology Students at Universitas Negeri Makassar - Jendri Mamangkey; Ahmad Sukarno Syahrir; Muhammad Wiharto; Muhiddin Palennari; La Ode Adi Parman Rudia (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Green Campus initiatives emphasize sustainable waste-management practices as an important component of institutional sustainability. Black Soldier Fly (BSF; Hermetia illucens) bioconversion has emerged as a promising approach for converting organic waste into value-added products while reducing environmental burdens. To support sustainability education and promote awareness of BSF-based organic waste management, BIOMAGIC (Bio-Maggot Innovative Guide for Green Integrated Campus) was developed as a digital flipbook integrating concepts of organic waste management, BSF bioconversion, and Green Campus implementation. This study aimed to evaluate the educational feasibility and user acceptance of BIOMAGIC among undergraduate biology students at Universitas Negeri Makassar (UNM). A developmental evaluation approach was conducted during a socialization activity held in June 2026. Data were collected using Google Forms through pre-test and post-test knowledge assessments and a perception questionnaire. A total of 35 participants completed the pre-test, whereas 21 participants completed the post-test and user evaluation questionnaire. Participants demonstrated high baseline knowledge regarding BSF-based organic waste management, with mean pre-test and post-test scores of 95.10% and 95.24%, respectively. Knowledge related to BSF biological characteristics and cultivation showed higher post-test percentages, whereas sustainability-related concepts exhibited comparatively lower scores. User evaluation indicated favorable responses toward BIOMAGIC, with an overall mean perception score of 4.46 on a five-point Likert scale. Visual design received the highest ratings, while qualitative feedback highlighted accessibility, systematic content organization, and support for independent learning as major strengths. The findings support BIOMAGIC as a feasible and well-accepted digital learning resource for promoting awareness of BSF-based organic waste management and Green Campus concepts among university students.